Esclerose Lateral Amiotrófica: Evolução Clínica e Erros no Diagnóstico - Rui Henrique da Cunha de Sa Braga (2020)
Introduction: Amyotrophic Lateral Sclerosis (ALS) is a heterogeneous disease, often difficult to diagnose. We intend to evaluate its progression, since the initial symptoms till diagnosis and subsequent evolution, measuring the delay and initial errors in the diagnosis with any unnecessary treatments/interventions. Methods: We analyzed the medical records of patients diagnosed with ALS, admitted between 2010 and 2018, in our institution. Initial symptoms and progression to clinical milestones were recorded. The existence of inappropriate previous diagnoses and unnecessary interventions was assessed. Results: Sixty-six patients with clinical onset at 62±10.8 years were studied; 9.1% with family history of the disease. The definitive diagnosis was established 14,5 months [1-79] after the onset of symptoms. Dysarthro-dysphonia, followed by dysphagia were the first milestones reached, followed by walking with support, non-invasive ventilation, PEG and, finally, inability to walk and tracheostomy. Twelve (18.2%) patients had an incorrect initial diagnosis, with 33.3% of cases being structural myelopathy and 33.3% mononeuropathies, starting Riluzole later (p=0,027); however, there was no difference in their survival. Half (9.1%) of patients with an incorrect diagnosis underwent surgery as a result of these errors. Discussion: The clinical characterization of the patients studied was in line with the reported in literature. Almost a fifth of patients received an incorrect initial diagnosis and half of these were, consequently, submitted to surgery. Conclusion: Errors in the diagnosis of ALS are frequent, leading to delays in diagnosis and unnecessary procedures, with probable implications for the risks, anguish and uncertainty to which patients and their families are subjected.